Adicción a las redes sociales en adolescentes - Ortiz Jaramillo, Clarisa Lizette (2023)
Social media addiction is a behavioral disorder characterized primarily by the uncontrollable need to be connected to social networks, which has become a serious public mental health concern because it dramatically affects the lives of those who suffer from it and those around them, with adolescents being a high-risk group. The objectives of this research are to describe the scientific evidence, identify daily usage times, and find the risk factors associated with social media addiction in adolescents. To achieve this, a non-experimental cross-sectional design with a mixed descriptive approach based on literature systematization was employed. The population consisted of all relevant scientific evidence, with 60 scientific articles retrieved from databases such as Dialnet, Elsevier, Scielo, Science Direct, Springer Open, Redalyc, and through search engines like Google Scholar, Pubmed, and Scopus. Using selection criteria and the PRISMA flowchart, a sample of 16 scientific articles was obtained. The research found that adolescents spend three or more hours on social media, and the most common associated factors are lack of parental control, psychological distress, low physical activity, easy internet access, and excessive alcohol consumption. In conclusion, there is clear scientific evidence on this issue, and providing a broader perspective serves as an important starting point and precedent for educators, parents, and healthcare professionals to implement prevention and treatment strategies for this mental health problem